Bibliotherapy: Reading OVID During COVID - Stip, Emmanuel; Östlundh, Linda; Abdel Aziz, Karim (Frontiers in Psychiatry, 2020)
An epidemic of an infectious disease such as the COVID-19 is often a source of emotional distress, even among those who have not been directly exposed to the disease. The period following the acute phase of the coronavirus epidemic, and the mitigation measures will likely be hardest for medical professionals in terms of psychological impact. Bibliotherapy is a systematic intervention regarding the use of carefully selected reading materials in order to help persons to cope with stress and personal problems. This therapy can be used easily during the pandemic. The review of evidence shows that this kind of interventions can be helpful in educational and clinical contexts. During the crisis, it can be an alternative to video, film entertainment and a transition from serious medical journal club to softer medical humanities experience. In this article, we summarized the historical background of the bibliotherapy. We also proposed a list of reading from different times, and cultures relating to pandemic, quarantine, symptoms, confinement, and social impacts (Camus, Moravia, London, Le Clezio etc.). Bibliotherapy can be a way for doctors and health care workers fighting in the frontline of the epidemic to find psychological support and for debriefing. Bibliotherapy can help Individuals that need support for emotional stress during the pandemic to verbalize their feelings and emotions and identify new ways of addressing problems.